"Birdbrains" should not be ignored in studying the evolution of g. (2017) - Pepperberg, Irene M.
Abstract: The authors evaluate evidence for general intelligence ( g ) in nonhumans but lean heavily toward mammalian data. They mention, but do not discuss in detail, evidence for g in nonmammalian species, for which substantive material exists. I refer to a number of avian studies, particularly in corvids and parrots, which would add breadth to the material presented in the target article.